Strategi Komunikasi Media Sosial dalam Meningkatkan Citra Merk - Adinda Prawityasari; Aninda Putri Nabila; Yohan Berntwen Hutagalung (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Along with the development and growth of digital technology, companies are able to align their goals with the current era, namely digitalization in order to maintain and survive the company. Social media or online are currently widely used in society and become a community need in carrying out their social life. Companies can take advantage of social media to improve brand image to be part of the interactions that people undergo. This research method is a literature review research, using a qualitative and conceptual approach. The analytical technique used is annotated bibliography. The results of the literature review show that social media communication strategies in improving brand image can be done creatively and innovatively. Awareness of certain brands to be able to become a brand image and consumers can remember and be included in the opportunity for consumers to need certain brands, namely by continuously doing a wider mix on social media. Because social media is more than one and continues to develop, it can be considered including: education about social media marketing, reliable human resources, and budget.